Market Orientation, Digital Capability, and Brand Image Driving Customer Loyalty: Evidence from Indonesian Retail MSMEs - Eny Nuraeni; Yusuf Rahman Al Hakim; Ghozali; Risa Amalia Muzrifah; Ulfa Rahmawati (RISK : Jurnal Riset Bisnis dan Ekonomi, 2026)
This study investigates how market orientation, digital capability, and brand image influence customer loyalty, with customer satisfaction as a mediating factor, within retail MSMEs. It aims to understand how internal organizational competencies and marketing strategies foster long-term customer relationships in a competitive and digitalized marketplace. Using a quantitative survey approach, data were collected from 160 customers of retail MSMEs, following the ten-times rule for 16 indicators. Analyses were conducted with PLS-SEM to assess measurement validity and structural relationships. Results indicate that brand image directly enhances both customer satisfaction and loyalty, while digital capability and market orientation affect loyalty indirectly through satisfaction. Moreover, customer satisfaction significantly mediates these relationships, serving as a critical mechanism by which organizational capabilities and strategies are translated into loyalty. The findings underscore the importance for MSMEs of strengthening brand image, advancing digital competencies, and maintaining market-oriented strategies to improve satisfaction and loyalty, offering both theoretical contributions to relationship marketing and practical guidance for managers in the digital era.